A conserved domain regulates interactions of the v-fps protein-tyrosine kinase with the host cell. - DeClue, J E (1987)
All cytoplasmic protein-tyrosine kinases (PTKs) share a noncatalytic domain, termed SH2, which comprises approximately 100 residues located immediately N-terminal to the kinase domain. A linker in the AX9m mutant of Fujinami avian sarcoma virus (FSV) introduces a dipeptide insertion into the SH2 domain of the P130gag-fps PTK, which abolishes its ability to transform Rat-2 cells. However, at 36 degrees C AX9m FSV elicits focus formation and agar colony formation in infected chicken embryo fibroblasts (CEF) with single hit kinetics. At 41.5 degrees C AX9m FSV is nontransforming for CEF, and the mutant is therefore both host and temperature dependent for transforming activity. Both in vitro and in vivo, the specific kinase activity of AX9m FSV P130gag-fps, measured by autophosphorylation and phosphorylation of exogenous substrates, correlated with transforming activity. The consequences of the AX9m mutation for enzymatic function and transforming activity therefore depend on the cellular environment in which the altered v-fps protein is expressed. We conclude that the SH2 domain directs the interaction of the P130gag-fps catalytic domain with cellular proteins such as substrates for phosphorylation or regulators of kinase activity important for its transforming ability.